RARE-27. DOUBLE MUTATIONS: DIFFERENT GERMLINE AND TUMOR MUTATIONS LEAD TO POOR OUTCOMES. (4th December 2020) - Hemenway, Molly; Nellan, Anan; Foreman, Nicholas; Suttman, Alexandra; Schneider, Kami
Abstract: BACKGROUND: As genetic testing for both germline and tumor mutations has increased in completeness, complexity, and availability, more mutations and their impact on patient outcomes have been identified. METHODS: A retrospective review of pediatric patients who have identified germline mutations and a different tumor mutation was conducted. Data collected included demographics, tumor type, germline mutation status, tumor mutation status, relapse status, and patient outcome. RESULTS: Six patients aged 8–13 years old (median age 10 years) were identified for analysis. Four patients had pilocytic astrocytoma and two had pilomyxoid astrocytoma. One of the patients with pilocytic astrocytoma also had MPNST diagnosed very early at age 9. The combination of germline/tumor mutations is as follows: Neurofibromatosis Type I (NF1)/BRAF v600e, NF1, CHEK2/MYB-QKI, NF1, Klinefelter, ATM, MUTYH, GPC3/BRAF-KIAA fusion, NF1/BRAF-KIAA (2 patients), and Marfan's/BRAF-KIAA. The number of relapses per patient following initial diagnosis range from 3–7 with an average of 3.3. Four of the patients are alive and on therapy, which two are deceased. The two deceased patients both had NF1/BRAF-KIAA fusions and pilocytic astrocytomas. CONCLUSIONS: Patients with differing and compounded germline and tumor molecular genetic mutations have worse outcomes. These patients have more relapses and death when compared to those patients with one mutation, either germline or tumor. Broad molecular testing and germline testing for mutations is crucial in determining patient risk for poor outcomes.